2015
DOI: 10.1016/j.joa.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Reduced systemic vascular resistance is the underlying hemodynamic mechanism in nitrate‐stimulated vasovagal syncope during head‐up tilt‐table test

Abstract: Presyncopal symptoms during NTG-stimulated HUTT are SVR mediated, not cardiac output mediated. This study challenges the conventional idea of a decrease in cardiac output mediated by NTG as the overriding cause of presyncopal symptoms during HUTT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…SVR is calculated as 80 * (MAP-CVP)/CO, where MAP is mean arterial pressure and CVP is central venous pressure. The normal values of SVR range from 800 to 1200 dynes s/cm 5 [4] , consistent with the original article [1] . SVRI is calculated as 80*(MAP-CVP)/CI, where CI is cardiac index [5] ; and the formula equals 80*(MAP-CVP)/(CO/BSA), where BSA is body surface area.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…SVR is calculated as 80 * (MAP-CVP)/CO, where MAP is mean arterial pressure and CVP is central venous pressure. The normal values of SVR range from 800 to 1200 dynes s/cm 5 [4] , consistent with the original article [1] . SVRI is calculated as 80*(MAP-CVP)/CI, where CI is cardiac index [5] ; and the formula equals 80*(MAP-CVP)/(CO/BSA), where BSA is body surface area.…”
supporting
confidence: 86%
“…The correct SVRI units should be presented as either dynes s/(cm 5 /m 2 ) or dynes s*m 2 /cm 5 . We estimated that the proper SVRI values in the study conducted by Kim et al [1] would range from 1900 to 2300 dynes s m 2 /cm 5 . We agree with the general results and conclusions of the article; however, the SVRI results should be recalculated.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…However, after successful vagal denervation, the vasodepressor response became obvious. Kim et al [10] recently assessed the determinants of VVS during glyceryl trinitrate-stimulated HUT and demonstrated that syncope might be related with systemic vascular resistance rather than cardiac output. In our case, HUT was demonstrated glyceryl trinitrate-stimulated vasodepressor response after CNA.…”
Section: Discussionmentioning
confidence: 99%